Verification of antibacterial activity to enamel surfaces of new type of surface coating. Issue 1 (April 2021) - Kumagai, Tetsuya; Kashiwamura, Haruko; Katsumata, Mari; Ozaki, Masao
Abstract: Objective: Prevention is difficult to decrease dental caries only via the partial application of fluoride. The GC Co. has developed a coating material adhesive containing fluoride and zinc. It is thought that this zinc has an effect which prevents dental caries. The aim of this study was to evaluate the influence of the Caredyne Shield® (CS) on biofilm generation by S. mutans, as compared to an acidulated phosphate fluoride (APF) gel. Materials and methods: We performed the comparative study of the biofilm inhibitory effect which used the enamel of bovine teeth. Specimens were separated into a control group, an APF gel group, and a CS group. Biofilms were generated by adherent S. mutans . We observed the antibacterial weigh by the creation state of Biofilms. Results: Significant difference was observed in the number of bacterial colonies formed after 24 h, the number of bacterial colonies formed from detached S. mutans from the CS-treated experimental group were fewer in number than in the other group (p < 0.01). The biofilm formed by S. mutans 72 h after dissemination on the enamel surface was visible by fluorescence microscopy (Live/Dead staining method) and under the scanning electron microscope, in the CS-treated group, no plastic structures were observed, as the models were free of the biofilm and only scattered S. mutans cells were observed. Conclusion: We showed in this study the efficacy of CS in controlling the formation of biofilm. From such a result, we conclude that CS is a novel anticaries agent.